Gut hormone release after intestinal resection. Issue 10 (October 1982) - Besterman, H S; Adrian, T E; Mallinson, C N; Christofides, N D; Sarson, D L; Pera, A; Lombardo, L; Modigliani, R; Bloom, S R
Abstract : To investigate the possible role of gut and pancreatic hormones in the adaptive responses to gut resection, plasma concentrations of the circulating hormones were measured, in response to a test breakfast, in patients with either small or large intestinal resection and in healthy control subjects. In 18 patients with partial ileal resection a significant threefold rise was found in basal and postprandial levels of pancreatic polypeptide, a fourfold increase in motilin, and more than a twofold increase in gastrin and enteroglucagon levels compared with healthy controls. In contrast, nine patients with colonic resection had a threefold rise in levels of pancreatic polypeptide only. One or more of these peptides may have a role in stimulating the adaptive changes found after gut resection.